Does Market Power Affect Banking Dividend Policy? Evidence from Nepal - Sahadev Bhatt (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
We attempt to explain how market power impacts bank dividend payment behaviors in Nepal by taking the sample from the commercial banking sector employing a panel data regression model. Using the Lerner Index (LI), a non-structural measure of market power or lack of competition, we found that market power inversely but statistically insignificantly affect dividend payment. This finding leads us to conclude that market power-a proxy of more or less competition is not an important and influencing factor to the dividend decisions in commercial banking sectors signifying that competition does not seem helpful in mitigating agency conflicts. It is also concluded that banking dividend payouts are not the result of the punitive influence of product market antagonism. Further, among other firm-specific determinants, bank size and leverage significantly positively whereas asset growth significantly negatively affect the dividend decision. However, profitability is found insignificant determinant of dividend payment. The paper enriches and contributes to the literature on banking dividend payout and helps to identify the key factors that affect banking dividend decision-making.  Keywords : Banks, Market competition, Market power, Lerner Index, Nepal